Defining and increasing employee efficiency : the case of Icelandair - Auður Sigvaldadóttir 1994- (2019)
The purpose of this single case study on Icelandair, an internationally operating airline from Iceland, is to analyze the key factors defining efficiency and how efficiency of their employees can be increased. This thesis works with a conceptual framework supporting that as a prospector in a competitive environment, Icelandair should pursue a strategy of efficiency (i.e. exploitation) as opposed to effectiveness (i.e. exploration) to gain sustained competitive advantage. Thus, both non-crew and crew employees completed an employee survey on efficiency. A factor analysis shows that for the non-crew employees, efficiency at work is defined by three factors; Management, Company support (direct and indirect) and Personal skills and group support. For the crew employees, efficiency at work is defined by two factors; Company support (direct and indirect) and Personal skills and group support. The difference between them lies primarily in the difference in management. The results from an independent samples t-test shows that, for most questions, non-crew employees scored significantly lower than the crew employees. This emphasizes the importance of Icelandair first improving the non-crew employees’ efficiency, by focusing on improved cooperation between different departments, making efficient use of its resources and using employees’ ideas and suggestions to do better. Following this, Icelandair can then improve the crew employees’ efficiency, by focusing on improving cooperation between departments, clarifying the Icelandair Group’s strategy and objectives and making efficient use of its resources. Icelandair now has a clear view of the factors defining efficiency for its non-crew and crew, as well as managerial propositions on how to more efficiently be able to use its resources and capabilities to compete in the airline industry. Key words: efficiency, strategy, competitive advantage, resources, organizational learning, Icelandair